Gait recognition and micro-expression recognition based on maximum margin projection with tensor representation. Issue 8 (November 2016) - Ben, Xianye; Zhang, Peng; Yan, Rui; Yang, Mingqiang; Ge, Guodong
Abstract We contribute, through this paper, to design a novel algorithm called maximum margin projection with tensor representation (MMPTR). This algorithm is able to recognize gait and micro-expression represented as third-order tensors. Through maximizing the inter-class Laplacian scatter and minimizing the intra-class Laplacian scatter, MMPTR can seek a tensor-to-tensor projection that directly extracts discriminative and geometry-preserving features from the original tensorial data. We show the validity of MMPTR through extensive experiments on the CASIA(B) gait database, TUM GAID gait database, and CASME micro-expression database. The proposed MMPTR generally obtains higher accuracy than MPCA, GTDA as well as state-of-the-art DTSA algorithm. Experimental results included in this paper suggest that MMPTR is especially effective in such tensorial object recognition tasks.